Exploring the Impact of Digital Transformation on Ghana's Tourism and Hospitality Industry - Ahiabu (University of Ghana, 2025)
Digital transformation uses digital technology tools to change a company's business model, products, or organizational structures, improving its operations, processes, and overall customer value proposition. Tourism and hospitality activities are needed for a nation's cultural, social, economic, and development, providing employment opportunities, earning foreign income, preserving communities' cultural and historical heritages, and conserving the environment. However, there seems to be little or no empirical research about digital transformation in Ghana's tourism and hospitality industry. The critical success factor theory was adopted for the study, which has not been used in previous studies concerning digital transformation. The study examines the impact of digital transformation on Ghana's tourism and hospitality industry. The research objectives are to determine the current state of digital transformation in Ghana's tourism industry, to explore the enablers and challenges hindering the adoption of digital technologies, and to assess the impact of digital technologies on digital transformation in the tourism and hospitality industry. A qualitative approach was adopted, and a convenient and judgmental technique was used to choose participants. A total of 15 participants were used for the study, and interviews were conducted to collect data. Furthermore, to address the research inquiries presented, the study employed Miles and Huberman's data analysis approach to scrutinize the information acquired from the interviews. The findings revealed that the term ‘Digital Transformation’ is new to most participants, although they used digital technologies in the firms. According to the findings, digital technologies used in Ghana’s tourism and hospitality industry include Facebook, Website,Instagram, Mobile phones, Laptops, Closed Circuit Television (CCTV) Cameras, Emails, Smartphones, digital televisions, and Property Management Systems (PMS). It was discovered that the adoption and use of these digital technologies have enhanced collaboration and communication among the various stakeholders in the industry. Digital transformation has led to decreased human involvement, fostering enhanced operational efficiency. The facilitators of this transformation include industrial and government support, operational compatibility, and the widespread availability and acceptance of digital technologies. Conversely, notable challenges encompass high data, airtime, and electricity costs, poor network coverage in urban and rural areas, and cyber-attacks. The study recommends that effective sensitization is needed to empower stakeholders to grasp the concept of digital transformation and excel in the swiftly changing digital landscape, fostering innovation and enhanced guest experiences. The Government should collaborate with telecommunication agencies to enhance internet accessibility and coverage. There is a need for stakeholder engagement on the causes of high data cost in Ghana and the possible means of making data affordable to enhance the digital transformation drive. There is also a need for more research in cybersecurity in the tourism hospitality industry to enhance the security effectiveness of digital payment platforms since firms are uncomfortable using payment systems due to frequent cyberattacks. The limitations of the study include varying Success Factor Theory constructs, focusing solely on service providers, and time constraints hindering deeper exploration of digital transformation impacts and causing brief, delayed participant interviews. Future studies in this domain would benefit from a mixed-method approach, blending qualitative and quantitative methods. Exploring the impact of digital transformation from customers' viewpoints may also provide insights into preferences and service interactions. Integrating Critical Success Factor theory with other frameworks will also expand understanding, contributing to valuable holistic analyses for academia and industry practitioners.
MPhil. Management Information Systems
Keywords: Digital transformation; digital technology; customer value proposition